Physiotherapy for respiratory and cardiac problems : adults and paediatrics - Ammani Prasad, S.; Pryor, Jennifer A. (Elsevier, 2008)
Suitable for undergraduate and postgraduate students, and for the clinicians working with patients with cardiac and respiratory problems, this title integrates the evidence with clinical practice and covers the whole patient lifespan - infants, children, adolescents and adults